Financing Higher Education in Palestine - Kuhail, Hisham; Hauptman, Arthur M. (International Higher Education, 2001)
Despite great obstacles over its relatively short threedecade history, Palestinian higher education has helped to meet the rising demand for further education, providing access in West Bank/Gaza to those who had been forcibly deprived of the chance to study abroad. But longstanding demographic and fiscal pressures, coupled with inadequately defined priorities and chronic economic and political problems only heightened by the recent turbulence, have led to a higher education system in fundamental need of repair. In recognition of these facts, the Ministry of Higher Education (MOHE) of the Palestinian National Authority (PNA) has decided to develop a financing strategy for the purpose of creating a more effective, accessible, efficient, and accountable higher education system.